2019
DOI: 10.1002/gea.21727
|View full text |Cite
|
Sign up to set email alerts
|

The “Flint Depot” of prehistoric northern Israel: Comprehensive geochemical analyses of flint extraction and reduction complexes and implications for provenance studies

Abstract: Recent research has demonstrated that the Eocene Timrat formation in northeasternIsrael, which appears as an extensive land "strip" west of and parallel to the Rift Valley, was a major source of prehistoric flint. This supposition is supported by three large-scale extraction and reduction (E&R) complexes identified within this region, which offer direct evidence of intense Lower and Middle Palaeolithic exploitation and limited Neolithic/ Chalcolithic activities. Here, we present a first comprehensive overview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…In addition, a large reference collection was specifically designed with the aim of interpreting the archaeological wear of NMO. This reference collection is made up of 81 experimental tools knapped on flint collected in the south-west ridge overlooking the Hula Valley 88 . Tools were knapped by an experienced knapper (M. Guardiola) at IPHES in an attempt to replicate the NMO artifacts.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a large reference collection was specifically designed with the aim of interpreting the archaeological wear of NMO. This reference collection is made up of 81 experimental tools knapped on flint collected in the south-west ridge overlooking the Hula Valley 88 . Tools were knapped by an experienced knapper (M. Guardiola) at IPHES in an attempt to replicate the NMO artifacts.…”
Section: Methodsmentioning
confidence: 99%
“…This pattern characterizes many Eurasian Paleolithic groups (e.g., Geneste, 1985;Féblot-Augustins, 1993. It has even been suggested that the same raw material sources/quarries had been recognized and utilized over tens of thousands of years (Gopher and Barkai, 2014;Finkel et al, 2019). If that scenario holds, it would suggest that (for each period) such locations may have served as places of meeting between "others, " i.e., individuals that belonged in a single mating system.…”
Section: Raw Materialsmentioning
confidence: 99%
“…The goal of this approach is to identify elemental features that discriminate geologic samples from one deposit from others to source the geological origin of the raw materials used to manufacture artifacts, often using multivariate statistics techniques of classification like discriminant analysis (DA; Moreau et al, 2019;O'Leary et al, 2017). For example, among the possible markers, rare-earth elements (REE: La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Sc and Y) have been shown to be particularly effective in discriminating different types of cherts and solving provenance issues (Elefanti et al, 2021;Finkel et al, 2019;Olofsson & Rodushkin, 2011;Ramacciotti et al, 2019a). Indeed, robust geochemical studies proved that different sedimentary environments distinguish chert through characteristic REE levels and fractionation (Murray, 1994) and they were used as provenance markers in studies carried out on a wide range of geoarchaeological materials (Aura Tortosa et al, 2020;Gallello et al, 2016;Lecuit et al, 2018;Ramacciotti et al, 2019bRamacciotti et al, , 2020.…”
Section: Assessment Of Lithic Raw Materials Procurementmentioning
confidence: 99%